The impact of PARPs and ADP-ribosylation on inflammation and host–pathogen interactions - Fehr, Anthony R. (Genes Dev, 2020)
Poly-adenosine diphosphate-ribose polymerases (PARPs) promote ADP-ribosylation, a highly conserved, fundamental posttranslational modification (PTM). PARP catalytic domains transfer the ADP-ribose moiety from NAD(+) to amino acid residues of target proteins, leading to mono- or poly-ADP-ribosylation (MARylation or PARylation). This PTM regulates various key biological and pathological processes. In this review, we focus on the roles of the PARP family members in inflammation and host–pathogen interactions. Here we give an overview the current understanding of the mechanisms by which PARPs promote or suppress proinflammatory activation of macrophages, and various roles PARPs play in virus infections. We also demonstrate how innovative technologies, such as proteomics and systems biology, help to advance this research field and describe unanswered questions.